2019
DOI: 10.21315/aamj2019.24.s1.10
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Quality of Education: A Case Study on an International Islamic School

Abstract: Private secondary schools that want to gain a competitive edge need to search for effective and creative ways to attract, retain, and foster stronger relationships with students. The decision of selecting a school by the parents for their kids is based on a multitude of factors that differ from one society to another depending on its culture, economic status, religion, and others. The objective of the present research is to identify and prioritise the factors that can enhance the quality of education in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The first component of great teaching that has strong evidence of impact on students' outcomes is content knowledge, and the most effective teachers have deep knowledge of the subjects they teach, and when teachers' knowledge falls below a certain level, it is a significant impediment to students' learning [39]. Knowledge of specialization area and years of teaching experience are major components of quality of teachers [40]. lecturers' competence comes from knowledge and skills acquired through right education and experience.…”
Section: Lecturer Competencementioning
confidence: 99%
See 1 more Smart Citation
“…The first component of great teaching that has strong evidence of impact on students' outcomes is content knowledge, and the most effective teachers have deep knowledge of the subjects they teach, and when teachers' knowledge falls below a certain level, it is a significant impediment to students' learning [39]. Knowledge of specialization area and years of teaching experience are major components of quality of teachers [40]. lecturers' competence comes from knowledge and skills acquired through right education and experience.…”
Section: Lecturer Competencementioning
confidence: 99%
“…Dimensions and Elements of the Three Variables for Development of Measurement Instruments Sources:[32,34,37,38,39,40,45] …”
mentioning
confidence: 99%
“…The teaching workload of higher education institutions is not limited to their regular teaching activities, such as giving lectures, preparing lesson plans, evaluating scripts, and attending training programs and conferences. In addition, they have to be involved in non-academic activities such as proctoring, coordinating various higher education institution activities, and taking on various administrative posts (Hosain, 2016;Islam et al, 2019). Moreover, higher education instructors' work performance is based on their dedication to the job, success in research and development, student achievement, and active communication involving international collaboration and networking (Le, 2021;Odero & Makori, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gómez and Valdés (2019) found that instructors' performance is assessed by higher education institutions to favor teacher learning over the practice to improve it. Therefore, the analysis and establishment of standards-setting appraisal are important, leading to the need to create a proposal for the professional development of instructors and improvement in education quality (Aliasghar et al, 2017;Gómez & Valdés, 2019;Islam et al, 2019;Prasetio et al, 2017). Tan et al (2019) investigated how higher education students in Malaysia evaluated their instructors based on noninstructional factors, namely physical attractiveness and psychological factors, which could affect students' perceptions regarding their instructors' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many Muslim parents send their children to Islamic schools in which Islamic identity as their core value in their education system is integrated with the national education system determined by the government. Religious value and character building, and Islamic environment provided by Islamic schools are dominant factors influencing parents' decision in choosing Islamic schools in countries where Muslims are majority (D. Hidayati & Rifa'i, 2020;Islam et al, 2019), even in those where they are not (Musharraf & Nabeel, 2015).…”
Section: A Introductionmentioning
confidence: 99%